DEHYDROGENAZE POLYMORPHISM AS A TOOL FOR EARLY SELECTION OF LOW VIGOUR ROOTSTOCK FOR SWEET AND SOUR CHERRY - Čolić, Slavica D; Fotirić Akšić, Milica M; Rakonjac, Vera S; Nikolić, Dragan T (Journal of Agricultural Sciences (Belgrade), 2017)
Correlation of dehydrogenase isoenzyme profile and plant/tree vigour of twenty genotypes belonging to genus Prunus, subgenus Cerasus, and four commercial rootstocks (Colt, Gisela 5, Gisela 6 and MaxMa 14), was investigated in this study. PCA was applied for the classification of the cherry rootstock based on vigor traits and polymorphism of isoenzymes in order to determine which dehydrogenase enzyme is the most useful in the preselecting process ofcherry rootstocks. The most influential variables which led to the separation of low vigorous from other genotypes were IDH, MDH and PGD. Since both significant and negative correlation observed between tree vigour and MDH, so as between tree vigour and PGD, those systems can be used for early selection of low vigour rootstocks. Our results suggest that association between low vigour and MDH genotype ab, provides a convenient marker that can be characterized even in the seedling stage, and could be applied in early rootstock selection and breeding programs